2023
DOI: 10.1097/aln.0000000000004480
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Point-of-care Bedside Monitoring for Acute Respiratory Failure

Abstract: Advanced respiratory monitoring involves several mini- or noninvasive tools, applicable at bedside, focused on assessing lung aeration and morphology, lung recruitment and overdistention, ventilation–perfusion distribution, inspiratory effort, respiratory drive, respiratory muscle contraction, and patient–ventilator asynchrony, in dealing with acute respiratory failure. Compared to a conventional approach, advanced respiratory monitoring has the potential to provide more insights into the pathologic modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 105 publications
(189 reference statements)
1
22
0
Order By: Relevance
“…Fourth, phrenic nerve capture was determined by palpation of the abdomen that is a less sensitive but a more practical method than using electromyogram. 33 conclusion This proof-of-concept study showed the feasibility of short-term diaphragm neurostimulation in conjunction with mechanical ventilation in ARDS patients. Diaphragm neurostimulation was associated with positive effects on lung mechanics and on hemodynamics.…”
mentioning
confidence: 65%
“…Fourth, phrenic nerve capture was determined by palpation of the abdomen that is a less sensitive but a more practical method than using electromyogram. 33 conclusion This proof-of-concept study showed the feasibility of short-term diaphragm neurostimulation in conjunction with mechanical ventilation in ARDS patients. Diaphragm neurostimulation was associated with positive effects on lung mechanics and on hemodynamics.…”
mentioning
confidence: 65%
“…Out of all the people hospitalized with COVID-19, 15–30% will go on to develop COVID-19-associated acute respiratory distress syndrome ( 42 ). In the supine position, pleural pressure develops along a vertical gradient from the non-dependent to the dependent chest, which is magnified in patients with ARDS ( 43 ). Therefore, it is beneficial to carry out the prone position for patients with ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…However, note that the model then operates on an artificial pleural pressure level, restricting its ability to represent actual lung stresses. As mentioned earlier, measured esophageal pressure qualitatively reflects pleural pressure behavior, although not quantitatively 62,63 . Thus, using measured esophageal pressure might equally introduce a discrepancy in absolute values.…”
Section: Discussionmentioning
confidence: 86%
“…62,63 Thus, using measured esophageal pressure might equally introduce a discrepancy in absolute values. Moreover, measurements in the esophagus are strongly influenced by various factors, 63 potentially leading to further inaccuracies. Despite these uncertainties, neither the parametrization nor the simulation results have been significantly compromised in this work.…”
Section: Discussionmentioning
confidence: 99%